A primatological perspective on human cultural origins: When did cumulative culture evolved in our lineage - Alba Motes-Rodrigo (Mètode Science Studies Journal: Annual Review, 2024)
Humans are one of the most successful species in the planet as we inhabit almost every ecosystem on Earth. This success has been attributed to our cultural proficiency, which allows us to store in the collective minds of our populations complex knowledge that no single individual could innovate on its own. In this way, we acquire most of our behavioural repertoire from experts in our communities and, contrary to any other species, we build upon this collectively-stored information to create novel solutions to face ever-more-challenging problems. This ratcheting of behavioural complexity has led to our culture being coined cumulative. The fact that not even our closest living relatives, the great apes, possess this type of culture begs the question of when did cumulative culture evolve in our lineage. In this piece, I discuss how the field of experimental primate archaeology has contributed to this question by describing several stone-tool experiments conducted with great apes.